The Paradox of E-Office Adoption in Indonesian Public Service with 24.000 Apps: Innovation or Prestige? - Nadia Safira; Haris Hanan (Jurnal Sosial Humaniora, 2024)
This study examines the adoption process of e-office systems in Indonesiangovernment agencies, driven by the ZI WBK/WBBM competition aimed atpromoting corruption-free bureaucratic areas. The research reveals thatduring the confirmation stage of e-office implementation, the focus shiftedfrom assessing true innovation to merely obtaining the WBK/WBBMdesignation. This emphasis on the title undermines the core goal of e-office—improving public service delivery through e-governance. The study identifiesfive key stages in the adoption process: knowledge acquisition, persuasion,decision-making, implementation, and confirmation. It suggests thatstakeholders may prioritize the incentive of the ZI title over a deeperunderstanding of the technology’s benefits. Additionally, conflictingregulations present challenges that hinder successful implementation. Thestudy concludes that a revised approach is needed, one that prioritizes userexperience, public service improvement, and the core functionalities of the eoffice. By focusing on these elements, stakeholders can ensure the systemenhances government transparency and efficiency. This qualitative researchuses case-based analysis, drawing on interviews with government employeesand IT personnel involved in the ZI WBK/WBBM implementation.